Мотивация персонала как фактор повышения эффективности производства (Путеводитель предпринимателя)
The current stage of economic reform in Russia is characterized by the fact that businesses operate in an environment of increasing demands of different socialgroups: trade unions, youth leagues, party movement, and so on. In this regard, especially important to create an effective system of incentives for workers.